2013
DOI: 10.2169/internalmedicine.52.9214
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width for Heart Failure

Abstract: The Authors Reply We appreciate Shinohara's highly suggestive letter regarding our study (1). He recommends evaluating the mean corpuscular volume (MCV) upon examination of the red blood cell distribution width (RDW) in order to obtain a precise understanding of the cause of anemia. He presumes that our study population exhibited clinical features of the super-elderly and that RDW values can be influenced by the hematological state of anemia of chronic disease (ACD) or anemia of inflammation (AI) induced by nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This finding provides a new predictor of potential cardiovascular risks. Recently, many studies suggest that elevated RDW is associated with the increased incidence of cardiovascular events [ 11 13 ]. Li et al found that RDW could predict the early renal function in hypertensive patients with a sensitivity of 76% and a specificity of 70% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding provides a new predictor of potential cardiovascular risks. Recently, many studies suggest that elevated RDW is associated with the increased incidence of cardiovascular events [ 11 13 ]. Li et al found that RDW could predict the early renal function in hypertensive patients with a sensitivity of 76% and a specificity of 70% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported to be related to outcome in cases of infection, especially sepsis (13).…”
Section: Discussionmentioning
confidence: 99%